2012
DOI: 10.3928/01477447-20111122-09
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Reamer–Irrigator–Aspirator May Reduce Tumor Dissemination During Intramedullary Fixation of Malignancies

Abstract: Intramedullary nail fixation is the treatment of choice for impending and pathologic fractures secondary to metastatic cancer; however, this procedure has been shown to cause systemic embolization of intramedullary contents. This article reports the use of the reamer-irrigator-aspirator (RIA) (Synthes, Paoli, Pennsylvania) instead of a standard femoral reamer to decrease tumor intravasation during femoral intramedullary nail fixation for impending or pathologic fractures.Twenty-one consecutive patients indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The reamer head is designed to firmly engage to the disposable tube assembly and drive shaft. Dissociation and/or breakage of the reamer head or driver shaft inside the canal while reaming has been rarely reported and in all cases the reamer head that had disengaged was successfully retrieved using the ball tip guidewire [7][8][9] . There are no reports of metal debris from the reamer head persisting in the intramedullary canal apart from this current situation presented herein therefore no alternative methods of extraction have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reamer head is designed to firmly engage to the disposable tube assembly and drive shaft. Dissociation and/or breakage of the reamer head or driver shaft inside the canal while reaming has been rarely reported and in all cases the reamer head that had disengaged was successfully retrieved using the ball tip guidewire [7][8][9] . There are no reports of metal debris from the reamer head persisting in the intramedullary canal apart from this current situation presented herein therefore no alternative methods of extraction have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Kanakaris et al, reported one case of reamer head dissociation due to poor connection of the reamer head to the reamer shaft [8] . Cipriano et al [7] , reported 2 cases and Eisenstein et al [9] , reported 5 cases of intraoperative breakage of the drive shaft causing head-shaft dissociation during reaming. In all reports, the head was easily removed by pulling it up using the ball tip guidewire, as in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cipriano et al 15 investigated the use of the RIA in the treatment of 21 patients with malignant femoral lesions and found they were able remove on average 16.7 cc (0.35--36 cc) of tumor in the reamings. The reamer-irrigator-aspirator (RIA) (Synthes, Paoli, Pennsylvania) has been proposed to decrease this risk.…”
Section: Choice Of Fixationmentioning
confidence: 99%
“…Indeed, preclinical large animal studies showed that application of the RIA system was associated with a reduced amount of FE [ 19 , 20 ] and lower systemic effects compared to conventional reaming [ 21 , 22 ]. Based on these findings, the RIA system has been applied to reduce intravasation of intramedullary content, such as malignancies [ 23 ], infections [ 24 ], and cement removal [ 25 ]. However, systematic reporting of the associated complications is essential; yet, surprisingly, no systematic review of the complications associated with the use of the RIA system has been conducted.…”
Section: Introductionmentioning
confidence: 99%